Development Of Android-Based Occupational Safety and Health Learning Media to Improve Understanding of Work Accidents for Vocational High School Students - Wegig Pratama; Bambang Sudarsono (VANOS Journal of Mechanical Engineering Education, 2024)
This research is based on the high risk of accidents faced by SMK students in the engineering and vocational fields, as well as the need to understand K3 principles before entering the world of work. This research aims to develop Android-based learning media to improve Vocational High School (SMK) students' understanding of occupational safety and health (OHS). This research is descriptive quantitative research using Research and Development (R&D) research design with the ADDIE development model, which consists of five stages namely analysis, design, development, implementation, and evaluation.  The research subjects were 72 grade XI students at SMK Muhammadiyah 2 Tempel, selected based on their involvement in industrial work practices. Data were collected through observation, interviews, questionnaires, and tests, with instruments in the form of observation guidelines, interview guidelines, questionnaires, and test sheets. Data analysis was carried out descriptively and inferentially to assess the effectiveness of the media, with a t-test to determine the difference in students OHS understanding before and after using the media. The results showed that this Android-based media significantly improved students OHS understanding, indicated by an increase in the comprehension test score from 60% to 85%. As many as 92% of students felt that their understanding of OHS materials had improved, and 88% of students stated that this media was easy to use. The impact of this research contributes to improving the quality of vocational education, especially in preparing students for safety risks in the work environment, as well as improving students' digital literacy. The findings provide practical implications for the development of technology-based learning media relevant to industry needs and are expected to serve as a model for other educational institutions in improving students OHS understanding.